Let's form the difference of the two expressions and see what we can learn.
(2y -x) -(2x -y) = 2y -x -2x +y = 3y -3x = 3(y -x)
Since y > x, this is positive, so 2y -x is greater than 2x -y.
49 is a square of 7 and 4 is a square of 2. To get 45 you need to subtract 7² and 2². Therefore, its the difference of squares.
The degree of a monomial is the sum of its exponents
4x^7y^3
exponents are 7 and 3
degree is : 7 + 3 = 10
Answer:
x = ± √3 = ± 1.7321
x = 1
x = -1
Step-by-step explanation:
If it correct can you give me Brainliest plz